2023
DOI: 10.3390/su15054185
|View full text |Cite
|
Sign up to set email alerts
|

Study on Seismic Response and Vibration Reduction of Shield Tunnel Lining in Coastal Areas

Abstract: The construction of subway tunnels in the coastal section is affected by special soil quality, with complex construction conditions of unstable soil and vulnerability to groundwater corrosion. The design difficulty of subway tunnels is greatly increased, and the safety performance in the event of an earthquake is greatly reduced. To study the changes in shield tunnel lining structure under earthquake and propose damping measures, ANSYS software is used to conduct tunnel soil numerical simulation. Firstly, stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…A study carried out on concrete pipe behavior during seismic shaking showed that, linear elastic and Mohr-Coulomb models had lower bending moments than hardening soil and hardening soil with small strain stiffness models [12]. Results of ANSYS for numerical simulations showed that, arch crown deformation at 3.8 cm and wall corner stress at 2.6 x 10 7 Pa [13]. A study on Delhi metro tunnel behavior under various dynamic loading cases showes that, combined earthquake and train motion cause larger displacements in soil and forces in tunnel liners compared to individual loads [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study carried out on concrete pipe behavior during seismic shaking showed that, linear elastic and Mohr-Coulomb models had lower bending moments than hardening soil and hardening soil with small strain stiffness models [12]. Results of ANSYS for numerical simulations showed that, arch crown deformation at 3.8 cm and wall corner stress at 2.6 x 10 7 Pa [13]. A study on Delhi metro tunnel behavior under various dynamic loading cases showes that, combined earthquake and train motion cause larger displacements in soil and forces in tunnel liners compared to individual loads [14].…”
Section: Introductionmentioning
confidence: 99%
“…Fig 13. show the absolute maximum horizontal displacements for monitoring points as the percentage ratio of tunnel diameter (δx/D%) for different soil states under static load and earthquake records.…”
mentioning
confidence: 99%
“…This is of central importance for seismic design in the case of metro systems, considering their significance for life safety and economy and that they are generally more vulnerable in soft-soil ground conditions [9]. With regard to the seismic resistance of shield tunnels in areas with soft soil, researchers have conducted a range of investigations, mainly focusing on the dynamic response of tunnel structures under complex soft-soil ground conditions with different earthquake intensities and site conditions and the corresponding seismic design measures [10][11][12]. However, the tunnel lining structure is simplified to a homogeneous circumferential ring in the above study, only the overall performance of the segment ring is taken into account, and the weak link of the shield tunnel connection is not taken into account, which is somewhat different from the actual structure.…”
Section: Introductionmentioning
confidence: 99%